Standardization of Decent Accommodation through Internal Regulations at UIN Sunan Gunung Djati - Mamat Rohimat (AMUYA: JOURNAL OF MANAGEMENT, 2026)
This policy paper provides an overview of UIN Sunan Gunung Djati Bandung facing serious challenges in the form of inconsistent implementation of Reasonable Accommodation for persons with disabilities, which structurally violates the principle of justice and the mandate of Law No. 8 of 2016. This service misalignment is rooted in the absence of a binding Standard Operating Procedure (SOP) across units and the existence of an unequal policy focus, where attention is only focused on physical accessibility while ignoring non-physical service standards and inclusive pedagogy (Universal Design for Learning). This paper uses a qualitative policy analysis method with a normative-regulatory approach, referring to the legal framework of PMA No. 1 of 2024 as the PTKI compliance standard. Problem analysis is prioritized using the USG framework and evaluation of alternative solutions using the William N. Dunn scoring model. The results of the analysis indicate that Accommodation Inconsistency and Service Fragmentation have the highest priority because of their direct impact on student rights. The policy evaluation confirms that regulatory solutions (SOP, UDL, and Harmonization Task Force) are the most effective and feasible. Therefore, it is recommended that the Chancellor immediately issue a Chancellor's Decree on the ratification of a comprehensive Standard Operating Procedure (SOP) for Appropriate Cross-Unit Accommodation. This policy should be supported by a Circular Letter mandating the integration of UDL principles and the establishment of an Internal Regulation Harmonization Task Force to ensure structural institutional synergy and accountability.